Playing Entropy Mastermind can Foster Children’s Information-Theoretical Intuitions - Özel, Elif; Nelson, Jonathan D.; Bertram, Lara; Martignon, Laura (Frontiers in Education, 2021)
Conceptual descriptions and measures of information and entropy were established in the twentieth century with the emergence of a science of communication and information. Today these concepts have come to pervade modern science and society, and are increasingly being recommended as topics for science and mathematics education. We propose a road plan for playful activities aimed at fostering intuitions about entropy and describe a primary school intervention that was conducted according to this plan. Fourth grade pupils (8-10 years) played a version of Entropy Mastermind with jars and colored marbles, in which a hidden code to be deciphered was generated at random from an urn with a known, visually-presented probability distribution of marble colors. Pupils prepared urns according to specified recipes, drew marbles from the urns, generated codes and guessed codes. Despite not being formally instructed in probability or entropy, pupils were able to estimate and compare the difficulty of different probability distributions used for generating possible codes.